Relationship Between Middle Workload Calculations and High Infant Mortality Rate in Primary Health Care Work Area Jember District - Endina Setyorini; Nur Hamim; Iis Hanifah (Sean Institute, 2023)
The main task of the midwifery profession is to support the reduction of the Infant Mortality Rate (IMR) through quality midwifery services. The midwife's job is not only as an implementer of midwifery services, but also as a manager, researcher, and educator in the community. This study aims to determine the relationship between the workload of midwives and the infant mortality rate in the work area of ​​the Jember District Health Center. The research method used is descriptive correlation with cross sectional time approach. The population in this study were midwives at the primary health care Jenggawah, Ajung, and Kemuningsari Kidul. The sample in this study used a total population of 35 midwives who worked in three health centers in Jember Regency. The instrument used in this study used a questionnaire and observation. Data analysis using Chi-Square statistical test. The results of the study showed that the workload was mostly in the heavy category of 19 respondents (54.3%). Most of the infant mortality rates were classified as high, 20 cases (57.1%). The results of the Chi-Square test obtained P Value = 0.000 (α: 0.05) there is a relationship between the work of midwives and the high infant mortality rate. So it can be said that there is a significant relationship between the workload of midwives and the infant mortality rate in the work area of ​​the Jember District Health Center. Advice for midwives is the need for effective and constructive self-management, because the heavy workload of midwives can be effectively controlled and can prevent the increasing infant mortality rate.